Open Minds, Bold Futures: Linking Readiness for Uncertainty and Optimism to Business Performance among Woman Entrepreneurs - Anita Lucrecia; Dewi Mustikasari Immanuel (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Global economic uncertainty lead to business challenges, particularly among women entrepreneurs. In Indonesia, more than half of MSME owners are women, making psychological capacities such as open-mindedness, uncertainty readiness, and optimism crucial determinants of business performance. The Previous studies report inconsistent findings, highlighting the urgency to understand the psychological capacities that support business performance. This study aims to analyze the effect of open-mindedness, uncertainty readiness, and optimism on women entrepreneurs business performance, and also analyzes the moderating role of optimism in these relationships. This research use quantitative approach, collecting data from 153 Indonesian women entrepreneurs who operated their businesses for at least one year, chosen via purposive sampling. Data were collected through an online questionnaire and analyzed using PLS-SEM. The findings show that open-mindedness, uncertainty readiness, and optimism contribute positive effects to business performance, but optimism does not act as a moderator between the relationships.